Analysis on English Slogan Of Fashion Label And Accessories - Anggarina, Dyah (2008)
The objectives of the study are describing the linguistic forms, describing the meaning and describing the types of English slogan of fashion label and accessories. The writer uses English slogans of fashion label and accessories as the data. For collecting the data, the writer uses documentation method. The data sources are fashion label and accessories sold in Matahari Departement Store, Point Break, and the advertisement in Break's News, Point Break monthly catalogue, and Ellegirl, fashion magazine, which contained English slogan. The data are analyzed according to their linguistic form, their type of meaning, and their type of slogan using type of slogan proposed by Franz. The results of this study are, first, the linguistic form of fashion label slogans are phrase (noun phrase) and sentences (declarative sentence and imperative sentence), whereas accessories slogans are in the form of phrases (noun phrase, verb phrase, and adjective phrase), and sentences (declarative sentence and imperative sentence). Second, the slogans of fashion label as well as those of accessories have conceptual meaning, connotative meaning and affective meaning. Third, the types of slogan of fashion label and accessories are unique feature, beneficial, and thought provoking.